Combination of D0 measurements of the top quark mass - Abazov, V. M. (2017)
We present a combination of measurements of the top quark mass by the D0 experiment in the lepton+jets and dilepton channels. We use all the data collected in Run I (1992-1996) at s=1.8 TeV and Run II (2001-2011) at s=1.96 TeV of the Tevatron pp collider, corresponding to integrated luminosities of 0.1 fb-1 and 9.7 fb-1, respectively. The combined result is: mt=174.95±0.40(stat)±0.64(syst) GeV=174.95±0.75 GeV.